Excitatory amino acid antagonists and pentylenetetrazol-induced seizures during ontogenesis. I. The effects of 2-amino-7-phosphonoheptanoate - Velísek, L; Kusá, R; Kulovaná, M; Mares, P (Life sciences, 1990)
The anticonvulsant action of 2-amino-7-phosphonoheptanoate (AP7) was assessed during ontogenesis of the rat. Animals of five age groups (7, 12, 18, 25, and 90 days) were pretreated with AP7 i.p. in the doses from 15 to 60 mg/kg 30 min prior to pentamethylenetetrazol (PTZ; metrazol; 100 mg/kg s.c.). The incidence and latency of minimal seizures (pure clonic without the loss of righting ability) and of generalized tonic-clonic seizures (major) were evaluated and compared with the control groups. Minimal metrazol seizures were not regularly observed in controls between ages 7 and 12 days. An increased incidence was noticed in AP7-treated groups. In animals of 18 days of age and older the AP7-pretreatment did not influence incidence of minimal seizures; the latencies were significantly lengthened only in 18-day-old animals. Major seizures were significantly suppressed with the highest dose of AP7 (60 mg/kg) in all groups except 7-day-old rats. In 90-day-old rats all doses of AP7 were effective in the suppression of major seizures. The latencies of major seizures were increased in 7 and 18 days old rats. It appears that the blockade of NMDA receptor substantially influences the major seizures induced by PTZ, whereas minimal (clonic) seizures are affected weakly. This suggests an important role of NMDA receptor-mediated transmission in the genesis of generalized tonic-clonic seizure pattern.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; 2-amino-5-fosfonovalerát; Pentylenetetrazole; záchvaty; Aging; Rats; pohybová aktivita; 2-Amino-5-phosphonovalerate; Male; Specific Pathogen-Free Organisms; receptory aminokyselin; Receptors, Cell Surface; antikonvulziva; mužské pohlaví; Seizures; krysa rodu Rattus; organismy bez specifických patogenů; stárnutí; zvířata; Anticonvulsants; Premedication; Receptors, Amino Acid; receptory buněčného povrchu; Motor Activity; pentylentetrazol; premedikace; aminokyseliny; Amino Acids; Animals